DISSOLUTION MECHANISMS OF WATER IN DEPOLYMERIZED SILICATE MELTS: CONSTRAINTS FROM 1H AND 29SI NMR SPECTROSCOPY AND AB INITIO CALCULATIONS - Xue X.; Kanzaki M. (My University, 2004)
Dissolution of water in magmas significantly affects phase relations and physical properties. To shed new light on the this issue, we have applied 1H and 29Si nuclear magnetic resonance (NMR) spectroscopic techniques to hydrous silicate glasses (quenched melts) in the CaO-MgO-SiO2 (CMS), Na2O-SiO2, Na2O-CaO-SiO2 and Li2O-SiO2 systems. We have also carried out ab initio molecular orbital calculations on representative clusters to gain insight into the experimental results.The most prominent result is the identification of a major peak at ∼1.1 to 1.7 ppm in the 1H MAS NMR spectra for all the hydrous CMS glasses. On the basis of experimental NMR data for crystalline phases and ab initio calculation results, this peak can be unambiguously attributed to (Ca,Mg)OH groups. Such OH groups, like free oxygens, are only linked to metal cations, but not part of the silicate network, and are thus referred to as free hydroxyls in the paper. This represents the first direct evidence for a substantial proportion (∼13∼29%) of the dissolved water as free hydroxyl groups in quenched hydrous silicate melts. We have found that free hydroxyls are favored by (1) more depolymerized melts and (2) network-modifying cations of higher field strength (Z/R2: Z: charge, R: cation-oxygen bond length) in the order Mg > Ca > Na. Their formation is expected to cause an increase in the melt polymerization, contrary to the effect of SiOH formation. The 29Si MAS NMR results are consistent with such an interpretation. This water dissolution mechanism could be particularly important for ultramafic and mafic magmas.The 1H MAS NMR spectra for glasses of all the studied compositions contain peaks in the 4 to 17 ppm region, attributable to SiOH of a range of strength of hydrogen bonding and molecular H2O. The relative population of SiOH with strong hydrogen bonding grows with decreasing field strength of the network-modifying cations. Ab initio calculations confirmed that this trend largely reflects hydrogen bonding with nonbridging oxygens.